Letter copies from Werner and Ida Gebhardt to Kasimir Fajans, January, 1939 - Bredig, Max Albert (1939)
Max Bredig (1902-1977) copies excerpts of letters addressed to his colleague, the chemistry professor Kasimir Fajans (1887-1985), from his family members in Germany, Werner and Ida Gebhardt. The Gebhardts, who have been persecuted under the Third Reich because of their Jewish heritage, are requesting advice on leaving Nazi-occupied Germany and immigrating to the U.S.A.
Keywords: Jewish Holocaust (1939-1945); Fajans, Kasimir, 1887-1975; Emigration and immigration; Bredig, Max Albert, 1902-1977; Jewish refugees